STRUCTURAL ANALYSIS OF MANGROVE COMMUNITIES ON THE CENTRAL QUEENSLAND COASTLINE - Saenger, P.; Robson, J. (Marine Research in Indonesia, 1977)
The mangrove communities of the Central Queensland coastline are structurally and floristically intermediate between the relatively simple, temperate mangrove communities to the south, and the more complex and luxuriant communities to the north. Climatically the central Queensland coastline is subtropical with a low (1011 mm) annual rainfall, falling mainly in the summer months; evaporation rates are high, particularly in winter. As a result of a four-metre tidal range and a gentlysloping depositional coastline, the areal extent of mangroves is large and most topographic and physiognomic types are represented. Twelve species of mangroves occur in the study area and although zonation is recognizable, the zones are neither constant nor discrete. In the Port Curtis area, three large plots (500 m2 have been established in which all mangroves have been numbered and tagged since January 1975. The results of the initial investigation of the plots are presented together with some of the changes noted on re-examination after 12 months.